2011
DOI: 10.1159/000321296
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Pharmacological Effects of Mitoxantrone and Acetyl-L-Carnitine in Mice with a Solid Form of Ehrlich Tumour

Abstract: Background: Dysfunction of the carnitine system in non-tumour tissue following anticancer therapy has been reported. In this setting, supplementation with carnitine derivatives might increase the general metabolic activity of normal cells so that they might better withstand the adverse effects of chemotherapy aimed at tumour cells. Here we investigated the effect of acetyl-L-carnitine (ALC) alone and in combination with the antineoplastic agent mitoxantrone (MX) in an animal cancer model. Methods: The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In contrast, the combination of L -carnitine with mitoxantrone in a mouse solid tumor model of Ehrlich tumor did not show a beneficial effect of L -carnitine. Here, Niang et al [48] reported a negative effect of L -carnitine on the therapeutic outcome of mitoxantrone. …”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the combination of L -carnitine with mitoxantrone in a mouse solid tumor model of Ehrlich tumor did not show a beneficial effect of L -carnitine. Here, Niang et al [48] reported a negative effect of L -carnitine on the therapeutic outcome of mitoxantrone. …”
Section: Discussionmentioning
confidence: 91%
“…Those higher doses, however, were associated with greater inhibitory effect on the growth of STE. Repeated doses of ALC alone were beneficial and produced a mean survival of 28.26 days (95% CI 19.21-41.57), about 58.8% longer than the untreated STE control group (17.81 days) [17]. Signs of toxicity in our experiments included decreased body weight gain and body weight loss.…”
mentioning
confidence: 54%
“…Ehrlich tumors are used largely in experimental cancer treatment, prevention, and modeling studies because tumor ocurrence rates after transplantation is very high and tumor growth is extremely rapid. On the other hand, a number of studies related to prevention of Ehrlich tumor (either ascites or solid subtypes) are few (Mashanova et al, 2010;Jukanti et al, 2011;Niang et al, 2011;Salem et al, 2011).…”
Section: Discussionmentioning
confidence: 99%